Racial Differences in Accepting Pegfilgrastim Onpro Kit (On-Body Injector) Use Among Cancer Patients - Saif, MW (Clin Oncol (Las Vegas), 2019)
1.1. BACKGROUND: Neulasta Onpro kit eliminates need for additional clinic visit after chemotherapy. Given the racially diverse population in our institution, we investigated acceptance of Onpro kit among patients on chemotherapy. 1.2. RESEARCH DESIGN AND METHODS: Single-institution, retrospective review conducted in patients with GI tumors who received Onpro kit within 1 hour of completion of systemic chemotherapy from Jan 2014 through Jan 2018. Clinic/nursing notes and pharmacy records were reviewed to identify patients who refused Onpro kit and to discern reasons for refusal, including racial reason. 1.3. RESULTS: Total 238 orders for kit were voided amongst 68 patients (Caucasian 41; African American 7; Spanish 3; Asian 17). Overall, 15/68 patients refused kit (22%) of these 87% were Asian. The reasons for refusal included dislike of bulky attachment to skin, request to place kit on stomach instead of arm, trepidation over unwitnessed administration of drug, fear of reaction, disposal at home, fear of pain, lack of confirmation of proper dose administration, and need for MRI. 1.4. CONCLUSIONS: While Onpro kit is an attractive alternative, 22% of patients with voided orders, mainly of Asian race, declined its application. We believe the current study represents the first look at important racial differences in accepting Onpro kit. Consideration of patients’ cultural heritage, race, ethnicity and education may facilitate communication between physicians and patients to achieve optimal cancer care.